Fluorescence-guided ureteral identification in robotic surgery for advanced endometriosis: a comparison of junior versus senior surgeons - Linda A. Alpuing Radilla; Qiannan Yang; Daniel Y. Lovell; Tamisa Koythong; Brooke Thigpen; Luis E. Delgadillo Chabolla; Qianqing Wang; Xiaoming Guan (Scientific Reports)
Abstract Identifying the ureters in patients with advanced endometriosis and severe pelvic adhesive disease can be challenging. Adhesiolysis along the deformed pelvic sidewall may increase the risk of prolonged operative time and incidental ureteral injury. This study aimed to evaluate the safety and surgical outcomes of using Indocyanine Green (ICG) under near-infrared fluorescence for intraoperative ureteral localization and preservation during robot-assisted laparoscopic surgery (RALS) for advanced endometriosis, comparing procedures performed by two junior surgeons to those performed by one senior surgeon. This was a retrospective observational case series conducted by three minimally invasive gynecologic surgeons (X.G., T.K., B.T.) at a single tertiary care center between August 2021 and January 2025. A total of 92 patients underwent RALS using ICG fluorescence; 44 surgeries were performed by two junior surgeons, and 48 by a senior surgeon. The senior group had a higher percentage of patients with complete cul-de-sac obliteration (56.3% vs. 18.2%, p = 0.001). Our primary surgical outcome, total operative time, was 233 min in the junior group and 348 min in the senior group, initially showing a significant difference. However, after adjusting for factors such as history of prior abdominal surgery, cul-de-sac obliteration, and additional procedures (resection of ovarian remnant, bowel shaving, oophorectomy, enterolysis) using multivariable linear regression analysis, no significant difference was observed between the two groups. Other perioperative outcomes—including patient characteristics, estimated blood loss, length of hospital stay, and postoperative pain at weeks 1, 2, and 3—were comparable between the groups. Complication rates did not differ significantly. Notably, there were no cases of temporary or permanent ureteral injury in either group. These findings suggest that with ICG-assisted ureteral mapping, junior surgeons can achieve comparable surgical outcomes to senior surgeons. ICG facilitates intraoperative ureter identification, with the potential to enhance surgical safety by improving surgical precision and supporting the training of junior surgeons in managing complex endometriosis.